2019
DOI: 10.1108/ecam-07-2018-0307
|View full text |Cite
|
Sign up to set email alerts
|

Construction delay risk taxonomy, associations and regional contexts

Abstract: Purpose The purpose of this paper is to systematically develop a delay risk terminology and taxonomy. This research also explores two external and internal dimensions of the taxonomy to determine how much the taxonomy as a whole or combinations of its elements are generalisable. Design/methodology/approach Using mixed methods research, this systematic literature review incorporated data from 46 articles to establish delay risk terminology and taxonomy. Qualitative data of the top 10 delay risks identified in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(41 citation statements)
references
References 102 publications
1
39
0
Order By: Relevance
“…Texts within P, and similarly within Q, show some variation, though all of them indicated similar issues and signify different ways in which related risks or claims occur. Derakhshanfar et al (2019) also observed similar variations in taxonomy of risks. For example, in P resettlement and rehabilitation (Keci, 2015), delays in obtaining site access (El-Sayegh, 2008), and late handing over of a site (Perera et al , 2009) are the three of many ways in which land acquisition risks can manifest in projects.…”
Section: Theory Development: Relationship Between Risks and Claimssupporting
confidence: 60%
“…Texts within P, and similarly within Q, show some variation, though all of them indicated similar issues and signify different ways in which related risks or claims occur. Derakhshanfar et al (2019) also observed similar variations in taxonomy of risks. For example, in P resettlement and rehabilitation (Keci, 2015), delays in obtaining site access (El-Sayegh, 2008), and late handing over of a site (Perera et al , 2009) are the three of many ways in which land acquisition risks can manifest in projects.…”
Section: Theory Development: Relationship Between Risks and Claimssupporting
confidence: 60%
“…where n i = the number of contracts for which the ith delay factor occurred and N = 120. Next, the S value was calculated by calculating the RII according to Equation (7). In this case, each of the four categories of the variable "percent increase in construction duration" was given a value of 1 to 4 according to the severity of the increase in construction duration.…”
Section: Application and Discussion Of Risk Assessment Modelsmentioning
confidence: 99%
“…The first step to preventing litigation is to identify the delay risks as early as practically possible in the course of a project, and then to manage them throughout. Researchers agree that poor risk management is one of the major reasons causing time and budget overruns, thus tarnishing the reputation of contractors and clients alike [6,7]. Without effective risk management, these adverse effects are perpetuated.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The universal delay risks and other delay risks that are more or less depending on the project location were determined. Also, it is realized that delays connected to equipment, sub-contractors and design drawings are highly connected to project planning, finance and owner slow decision-making, respectively (Derakhshanfar et al , 2019). In an article entitled “The Project Strategy Matrix Systematizing the Design and Management of an Explicit Project Strategy,” to guide the balanced mixture of profound thought and coherent actions that are required in effectively establishing a project's specific course of action; as important input to the process of devising and controlling a project's execution plan; and as a valuable means to consistently communicate a project's key decisions so that to drive project-wise alignment and reduce uncertainty in operational decision-making.…”
Section: Literaturementioning
confidence: 99%